Blended Learning-Based Self-directed Learning on Classroom Action Research Training to Improve Teacher Competency Research - Gunawan Setiadi Sunardi; Soetarno Joyoatmojo; Sajidan Sajidan; Soeharto Soeharto (Journal of Education and Learning (EduLearn), 2016)
Abstract: Although classroom action research (CAR) is considered useful for teacher development but this activity has not been implanted yet effectively in Indonesia. In this paper, we report the alternative way to overcome this problem. It addresses how blended learning support self-directed learning and enhance teacher competency research. Through questionnaire, interview and document analysis, the result showed that blended learning-based self-learning can improve teachers performance in conducting classroom action research (CAR) and enhance their ability in compiling the research report.